Nationwide Biomonitoring of Neonicotinoid Insecticides in Breast Milk and Health Risk Assessment to Nursing Infants in the Chinese Population - Chen, Dawei; Liu, Zhibin; Barrett, Holly; Han, Jiajun; Lv, Bing; Li, Yan; Li, Jingguang; Zhao, Yunfeng; Wu, Yongning (Journal of agricultural and food chemistry, 2020)
Presently, the potential health risks of neonicotinoid insecticides (neonics) are now receiving much attention, but no data regarding the exposure of infants to neonics via human breast milk intake have been reported. In this study, a nationwide survey was conducted during the period of 2017–2019, wherein 97 pooled breast milk samples were collected from 3570 lactating women of 23 provinces in China. Nationally, acetamiprid-N-desmethyl was the most predominant compound, accounting for 61.2% of the total amount of neonics, followed by imidacloprid (15.6%). The concentration of the sum of acetamiprid and its metabolite acetamiprid-N-desmethyl in breast milk was positively correlated with corresponding dietary exposure, while no statistically significant association between the other neonic levels in breast milk and dietary exposure was found. The cumulative daily intakes of neonics (9.40–249 ng kg–1 of body weight day–1) were estimated for breastfed infants, indicating a minuscule risk to Chinese infants from neonic exposure via breastfeeding.